1996
DOI: 10.3109/09513599609041265
|View full text |Cite
|
Sign up to set email alerts
|

Superovulation with urinary human follicle-stimulating hormone: correlations with body mass index and body fat distribution

Abstract: Our objective was to investigate the relationship between body mass index (BMI), waist/hip ratio (WHR), follicle-stimulating hormone (FSH) dose, length of stimulation and clinical outcome in infertile women with and without polycystic ovary syndrome (PCOS) undergoing controlled ovarian hyperstimulation. Controlled ovarian hyperstimulation was induced in 60 women for a total of 111 cycles (48% in PCOS patients) with urinary human FSH (u-hFSH). A significant correlation between BMI, u-hFSH dose and duration of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…This phenomenon has already been described (16,17) using clomiphene citrate treatment: with increasing body weight the dose of clomiphene citrate had to be increased progressively, and there was a positive correlation between clomiphene citrate dose and body weight. BMI also was found to be significantly correlated with both the number of FSH ampoules administered and the length of stimulation (8). In this study, the number of collected oocytes significantly decreased with an increase of BMI.…”
Section: Response To Ovarian Stimulation Protocolsupporting
confidence: 57%
“…This phenomenon has already been described (16,17) using clomiphene citrate treatment: with increasing body weight the dose of clomiphene citrate had to be increased progressively, and there was a positive correlation between clomiphene citrate dose and body weight. BMI also was found to be significantly correlated with both the number of FSH ampoules administered and the length of stimulation (8). In this study, the number of collected oocytes significantly decreased with an increase of BMI.…”
Section: Response To Ovarian Stimulation Protocolsupporting
confidence: 57%
“…requirement during COH [4,5,[14][15][16][17]; decreased serum estradiol concentrations [7,16]; and a lower number of retrieved oocytes [16,18]. Moreover, other studies have also reported that, in women younger than 35 years, a higher BMI was negatively associated with the number of retrieved mature oocytes as well as fertilization, implantation, pregnancy, clinical pregnancy, and live birth rates [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Central adiposity (android fat distribution) has more impact on the reproductive sequelae associated with obesity (Norman and Clark, 1998). Zullo et al (1996) suggested that a doubling of gonadotrophin dose was necessary for adequate ovarian stimulation in non-PCOS obese patients with a waist:hip ratio of 0.8 or more. Furthermore, Wass et al (1997) reported that women with an android fat distribution, defined as a waist:hip ratio Ͼ0.8, had less than half the pregnancy rate of those with gynaecoid body shape in IVF-embryo transfer treatment.…”
Section: Discussionmentioning
confidence: 99%